Osmium–Nitrosyl Oxalato‐Bridged Lanthanide‐Centered Pentanuclear Complexes – Synthesis, Crystal Structures and Magnetic Properties1. Issue 9 (16th February 2015) - Gavriluta, Anatolie; Claiser, Nicolas; Kuhn, Paul‐Steffen; Novitchi, Ghenadie; Tommasino, Jean Bernard; Iasco, Olga; Druta, Vadim; Arion, Vladimir B.; Luneau, Dominique
Abstract: A series of pentanuclear heterometallic coordination compounds of the general formula (Bu4 N)5 [Ln{Os(NO)(μ‐ox)Cl3 }4 (H2 O) n ] [Ln = Y (for2 ) and Dy (for3′ ) when n = 0; Ln = Dy (for3 ), Tb (for4 ), and Gd (for5 ) when n = 1] were synthesized by the reaction of the precursor (Bu4 N)2 [Os(NO)(ox)Cl3 ] (1 ) with the respective lanthanide(III) (Gd, Tb, Dy) or yttrium(III) chloride. For the five new complexes, the coordination numbers eight or nine are found for the central metal ion. The compounds were fully characterized by elemental analysis, IR spectroscopy, single‐crystal X‐ray diffraction analysis, magnetic susceptibility measurements, and ESI mass spectrometry. In addition, compound1 was studied by UV/Vis spectroscopy and cyclic voltammetry. The X‐ray diffraction analyses revealed that the anionic complexes consist of a lanthanide or yttrium core bridged through oxalato ligands to four octahedral osmium–nitrosyl moieties. This picture, in which the central ion is eight‐coordinate, holds for lanthanide ions with an ionic radius smaller than that of the dysprosium(III) ion. For larger ionic radii, the central metal ion is nine‐coordinate, as the coordination sphere is completed by one molecule of water. Only in the case of dysprosium(III), it was possible to obtain complexes with both coordination numbers 8 and 9. This implies that dysprosium(III) is the tilt limit between the two coordination numbers in this series. The bond length Ln–O decreases from Dy to Gd. The nine‐coordinate complexes are energetically more favored for lanthanide ions with a radius larger than that of the dysprosium(III) ion, and the eight‐coordinate complexes are favored for smaller ions. Magnetic studies of the series of compounds showed that the osmium precursor1 as well as the yttrium compound2 are diamagnetic, whereas the magnetism of the gadolinium, terbium, and dysprosium complexes is due to isolated lanthanide ions. Abstract : Coordination tilt: Depending on the size of the Ln(III) ion, osmium–nitrosyl oxalato‐bridged lanthanide‐centered pentanuclear complexes exhibit two different coordination numbers, 8 or 9, for the central lanthanide ion, and both numbers are observed for dysprosium.